Business Essentials, Global Edition - Ebert, Ronald J.; Griffin, Ricky W. (Pearson International Content, 2025)
For introductory business courses. A focus on the practical skills and important developments in business Recent economic events are presenting unprecedented challenges, excitement and disappointments for businesses. They’re also uncovering a need for change in introduction to business courses and texts. Business Essentials captures the widespread significance of these developments and presents their implications for companies today. New coverage in the 14th Edition looks at changing employment relationships, changing labor relations and demographics, inflation and ESG. Students also see how entrepreneurs are putting into practice the concepts they’re learning about.